Field reports form for submitting seasonal observations of Iowa birds, Jim Sinclair, fall 1995 - Sinclair, Jimet al (1995)
List of birds and locations contributed by Jim Sinclair. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1995. Epson - sheet feed/flatbed